2021
DOI: 10.25217/jed.v1i02.1665
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Paragraph Shrinking Technique in Teaching Reading to Junior High School

Abstract:   The main problem of this research was focused on the effective teaching reading comprehension by using paragraph shrinking technique to eight grade students at SMP Negeri 1 Bumi Agung. The objective of this thesis is to know the effectiveness of teaching reading comprehension by using paragraph shrinking technique to eight grade students at SMP Negeri 1 Bumi Agung. In writing this research, the researcher used experimental method. The researcher used two groups of students namely control group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This is an effective strategy to train students to comprehend a text (Preast et al, 2019). Some studies have also shown the effectiveness and significant effect of using the paragraph shrinking strategy in improving students' reading skills (see, for example, Ridianto, 2018;Mardhaty, 2018;Sagita, 2021). This present research, therefore, is intended to see the effectiveness of the paragraph shrinking strategy, specifically in understanding general information, detailed information, reference, and vocabulary in reading skills.…”
mentioning
confidence: 91%
“…This is an effective strategy to train students to comprehend a text (Preast et al, 2019). Some studies have also shown the effectiveness and significant effect of using the paragraph shrinking strategy in improving students' reading skills (see, for example, Ridianto, 2018;Mardhaty, 2018;Sagita, 2021). This present research, therefore, is intended to see the effectiveness of the paragraph shrinking strategy, specifically in understanding general information, detailed information, reference, and vocabulary in reading skills.…”
mentioning
confidence: 91%